An optimized ChIP‐Seq framework for profiling histone modifications in Chromochloris zofingiensis. (28th March 2022) - Strenkert, Daniela; Mingay, Matthew; Schmollinger, Stefan; Chen, Cindy; O'Malley, Ronan C.; Merchant, Sabeeha S.
Abstract: The eukaryotic green alga Chromochloris zofingiensis is a reference organism for studying carbon partitioning and a promising candidate for the production of biofuel precursors. Recent transcriptome profiling transformed our understanding of its biology and generally algal biology, but epigenetic regulation remains understudied and represents a fundamental gap in our understanding of algal gene expression. Chromatin immunoprecipitation followed by deep sequencing (ChIP‐Seq) is a powerful tool for the discovery of such mechanisms, by identifying genome‐wide histone modification patterns and transcription factor‐binding sites alike. Here, we established a ChIP‐Seq framework for Chr. zofingiensis yielding over 20 million high‐quality reads per sample. The most critical steps in a ChIP experiment were optimized, including DNA shearing to obtain an average DNA fragment size of 250 bp and assessment of the recommended formaldehyde concentration for optimal DNA–protein cross‐linking. We used this ChIP‐Seq framework to generate a genome‐wide map of the H3K4me3 distribution pattern and to integrate these data with matching RNA‐Seq data. In line with observations from other organisms, H3K4me3 marks predominantly transcription start sites of genes. Our H3K4me3 ChIP‐Seq data will pave the way for improved genome structural annotation in the emerging reference alga Chr. zofingiensis .